A 2-hour Accelerated Chest Pain Protocol to Assess Patients with Chest Pain Symptoms in an Accident and Emergency Department in Hong Kong. Issue 5 (September 2013) - Ko, HF; Lee, HY; Ho, HF
Background: The present study is a follow up analysis of ASPECT study. We aimed to prospectively validate a 2-hour accelerated chest pain protocol (ACPP) to assess patients presenting to emergency department with chest pain symptoms suggestive of acute coronary syndrome. Methods: This observational study was carried out between June 2009 and July 2010. Patients were included if they were older than 18 years old and presented with at least 5 minutes duration of chest pain. The ACPP included modified Thrombolysis in Myocardial Infarction score, electrocardiograph and point-of-care troponin I at presentation and 2-hour after. Primary endpoint was major adverse cardiac event (MACE) at 45-day of initial hospital attendance. Results: A total of 384 Chinese patients were recruited and completed 45-day follow up. Forty-five (11.7%) had 45-d MACE. The ACPP identified 124 (32.3%) low risk patients who could be discharged early. No MACE occurred within 45 days among these patients, giving a sensitivity of 100% (95% CI 90-100), a negative predictive value of 100% (96-100), and a specificity of 36.6% (31.5-42). Conclusions: The ACPP is able to identify very low risk chest pain patients who might be suitable for early discharge without increasing risk of developing MACE. The observation period can be shortened to 2-hour of ED presentation. The variables are objective and easily available. This 2-hour Hong Kong Chest Pain Rule is applicable to Chinese population and has the potential to change the current practice in Emergency Departments in Hong Kong and China.